Challenges for Spheromak Confinement at Fusion Relevant Temperatures - Carlos Romero-Talamás; J B O ‘Bryan; Simon Woodruff (My University, 2015)
The spheromak is a self-organized, magnetized plasma configuration with currents approximately aligned with the magnetic field (~ j

B) that has long been considered as a viable and economical candidate to confine fusion-grade plasma. Its advantage over the more studied tokamaks and stellarators stems from its engineering simplicity since it does not require expensive superconducting coils, the plasma volume is simply connected, and a commercial reactor is expected to be at least an order of magnitude smaller than that of a tokamak. The research frontier is to demonstrate the viability of the spheromak to confine thermonuclear fusion plasmas for times that are long enough to test alpha heating, auxiliary heating, and engineering issues such as wall loading from plasma and neutrons, and dusty plasma generation and redeposition.